2019
DOI: 10.3390/rs11192327
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Targets above the Earth’s Surface Using GNSS-R Delay Doppler Maps: Results from TDS-1

Abstract: Global Navigation Satellite System (GNSS) reflected signals can be used to remotely sense the Earth’s surface, known as GNSS reflectometry (GNSS-R). The GNSS-R technique has been applied to numerous areas, such as the retrieval of wind speed, and the detection of Earth surface objects. This work proposes a new application of GNSS-R, namely to detect objects above the Earth’s surface, such as low Earth orbit (LEO) satellites. To discuss its feasibility, 14 delay Doppler maps (DDMs) are first presented which con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…It appears that from the CRB presented in this contribution, it is possible to deduce the specific scenario studied in [28]. However, in other scenarios, the Doppler shifts of the LOS and the NLOS signals may be different (e.g., if the signal is reflected from a moving object [47]) and a more general approach is needed, for which the result in [28] is not valid and the proposed CRB provides an answer.…”
Section: Comparison With Existing Literaturementioning
confidence: 95%
“…It appears that from the CRB presented in this contribution, it is possible to deduce the specific scenario studied in [28]. However, in other scenarios, the Doppler shifts of the LOS and the NLOS signals may be different (e.g., if the signal is reflected from a moving object [47]) and a more general approach is needed, for which the result in [28] is not valid and the proposed CRB provides an answer.…”
Section: Comparison With Existing Literaturementioning
confidence: 95%
“…(6) Remove other noises: Hu et al reported 14 DDM data with anomalies [35]. These abnormal data contain not only the normal DDM waveform but also abnormal bright spots and other weak signals.…”
Section: Data Quality Controlmentioning
confidence: 99%
“…Objects on the Earth's surface that are susceptible to being detected using GNSS-R instruments include sea ice [39], manmade objects on the sea surface [14,15], oil slicks [40], etc. Their detection is based on the difference of the reflection coefficient between the sea around it and the target.…”
Section: Target Detectionmentioning
confidence: 99%
“…This technology has been proven to work in five space-based missions: UK-DMC [2], TDS-1 [3,4], CYGNSS [5,6,7], BF-1 [8], and more recently FSSCat [9]. The former was only a proof-of-concept mission that demonstrated the capabilities and potential of GNSS-R from space, whereas TDS-1 and CYGNSS have provided a wealth of GNSS-R data that has been successfully used for sea state retrieval [4], sea ice detection [10], soil moisture [11,12,13], target detection [14,15], and waste on the ocean surface, among others.…”
Section: Introductionmentioning
confidence: 99%